Mansonella, including a Potential New Species, as Common Parasites in Children in Gabon. - Gaël Mourembou; Florence Fenollar; Jean Bernard Lekana-Douki; Angelique Ndjoyi Mbiguino; Sydney Maghendji Nzondo; Pierre Blaise Matsiegui; Rella Zoleko Manego; Cyrille Herve Bile Ehounoud; Fadi Bittar; Didier Raoult; Oleg Mediannikov (Public Library of Science (PLoS), 2015)
Like other tropical African countries, Gabon is afflicted by many parasitic diseases, including filariases such as loiasis and mansonellosis. This study aimed to assess the prevalence of these two filarial diseases in febrile and afebrile children using quantitative real-time PCR and standard PCR assays coupled with sequencing.DNA from blood specimens of 1,418 Gabonese children (1,258 febrile and 160 afebrile) were analyzed. Overall, filarial DNA was detected in 95 (6.7%) children, including 67 positive for M. perstans (4.7%), which was the most common. M. perstans was detected in 61/1,258 febrile children (4.8%) and 6/160 afebrile children (3.8%, P = 0.6). Its prevalence increased statistically with age: 3.5%, 7.7% and 10.6% in children aged ≤ 5, 6-10 and 11-15 years, respectively. M. perstans prevalence was significantly higher in Koulamoutou and Lastourville (12% and 10.5%, respectively) than in Franceville and Fougamou (2.6% and 2.4%, respectively). Loa loa was detected in seven febrile children including one co-infection with M. perstans. Finally, 21 filarial DNA positive were negative for M. perstans and Loa loa, but ITS sequencing could be performed for 12 and allowed the identification of a potential new species of Mansonella provisionally called "DEUX". Mansonella sp. "DEUX" was detected only in febrile children.Further study should be performed to characterize Mansonella sp. "DEUX" and evaluate the clinical significance of mansonellosis in humans.